Higher frequencies of functional HIV-envelope-specific memory B cells are associated with nonprogressive HIV infection in Indian population. (1st September 2020) - Dhande, Jayshree R.; Saikia, Kasturi; Singh, Dharmendra P.; Bagul, Rajani D.; Kulkarni, Smita S.; Ghate, Manisha V.; Thakar, Madhuri R.
Abstract : Objective: The HIV-1-specific antibodies are being considered for prevention and therapy in HIV infection. For effective antibody response, presence of functionally competent memory B cells (MEBs) is important; however, HIV-infection is known to alter the B-cell functionality. Very limited data are available on the HIV-specific memory B-cell population in HIV-infected Indian population. Methods: In this study, the frequencies of HIV-gp140-specific MEBs were measured in individuals with nonprogressive [long-term-nonprogressors (LTNPs), N  = 20] and progressive ( N  = 19) HIV infection using multicolor flow cytometry. The activation and functional status of these MEBs were assessed as frequencies and mean fluorescence intensity (MFI) of the CD38 and CD40 expression, respectively. Results: The percentages of gp140 + MEBs were higher in LTNPs than seen in progressors ( P  = 0.0475) and associated with higher CD4 + cell count ( P  = 0.0312, r  = 0.2833). As compared with the progressors, LTNPs also showed higher functional (CD40+) gp140 + MEBs both frequencies ( P  < 0.0001) and CD40 MFI ( P  = 0.0222), whereas the frequencies (<0.0001) and the MFI ( P  = 0.0047) of CD38 expression was significantly lower. Higher CD4 + cell counts and lower plasma viral load values were associated with higher frequencies of CD40+ gp140 + MEBs ( P  < 0.0001, r  = 0.4962) ( P  = 0.0036, r  = −0.4202) and lower frequencies ( P  = 0.0008, r  = −0.4231) and CD38 expression (MFI) ( P  = 0.004, r  = −0.3719) ( P  = 0.0066, r  = 0.4033). Conclusion: Our study suggests that LTNPs have functional HIV-specific memory B-cell compartment with reduced activation that may lead to effective HIV-specific humoral immune responses contributing to their nondisease progression status. These findings would help in better understanding of the characteristics of the HIV-specific memory B-cell population in nonprogressive HIV infection. Abstract : Supplemental Digital Content is available in the text